The Influence of EDI-Based Organizational Justice on Employee Retention at Hospital X - Shara, Anisya Indra; Ginting, Angel Christmas Thania; Bangun, Wilson (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to examine the effect of organizational justice on employee retention through the application of Equity, Diversity, and Inclusion (EDI) principles at Hospital X in Bandung City. The identified problem is the low retention rate of permanent employees, which has the potential to disrupt the hospital’s operational effectiveness. Organizational justice is analyzed through three main dimensions: distributive, procedural, and interactional justice, within the context of Indonesia’s work culture, which tends to be hierarchical and collectivist. EDI is used as a conceptual framework to assess the contribution of a fair and inclusive work environment to employee loyalty. The study employs a quantitative approach using a survey method. The research population consists of all permanent employees of Hospital X, with a sample of 286 respondents selected using purposive sampling based on Slovin’s formula. The research instrument is an online questionnaire, and the data were analyzed using linear regression. The findings reveal that organizational justice has a positive effect on EDI implementation, and EDI significantly influences employee retention. Furthermore, EDI serves as a mediator in the relationship between organizational justice and retention, highlighting the importance of justice- and inclusivity-based managerial strategies in enhancing workforce sustainability.